Blastic Plasmacytoid Dendritic Cell Neoplasm Following Acquired Erythropoietic Protoporphyria. Issue 4 (1st October 2017) - Krause, John R.; Baugh, Laura; Swink, Alicia; Burch, Micah
Abstract : A 56-year-old Texas rancher with a prior diagnosis of acquired erythropoietic protoporphyria secondary to an underlying myelodysplastic disorder developed an uncommon tumor, blastic plasmacytoid dendritic cell neoplasm (BPDCN). During his initial disease, analysis revealed a TET2 mutation, which is the most common mutation associated with BPDCN. This article discusses this unusual hema-topoietic neoplasm, the possible evolution from erythropoietic protoporphyria, and the underlying myelodysplastic process.